2000
DOI: 10.1159/000014474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>L</i>-Carnitine Supplementation on Renal Anemia in Poor Responders to Erythropoietin

Abstract: While renal anemia can be successfully treated by use of erythropoietin (EPO) in most hemodialysis (HD) patients, some patients have anemia that is refractory to treatment with a high dose of EPO. We examined whether L-carnitine treatment could raise hematocrit (Hct) levels in such patients. Fourteen HD patients who showed a poor response to EPO and no evident factors which inhibit a response to EPO were selected to receive oral L-carnitine (500 mg/day) in a 3-month trial. During the study, 36% of the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 23 publications
3
27
0
3
Order By: Relevance
“…Recently, Lcarnitine has been proposed as a potential adjuvant treatment to improve anaemia, thrombocytopenia, leukopenia and immunological function. [68][69][70][71][72][73] In a recent study, L-carnitine added to Peg-IFN-α plus ribavirin led to less decrease of platelet count during antiviral therapy. 74 Some studies indicate that L-carnitine modulates platelet functions and production through antioxidant mechanisms and the inhibition of the arachidonic acid cascade.…”
Section: L-carnitinementioning
confidence: 98%
“…Recently, Lcarnitine has been proposed as a potential adjuvant treatment to improve anaemia, thrombocytopenia, leukopenia and immunological function. [68][69][70][71][72][73] In a recent study, L-carnitine added to Peg-IFN-α plus ribavirin led to less decrease of platelet count during antiviral therapy. 74 Some studies indicate that L-carnitine modulates platelet functions and production through antioxidant mechanisms and the inhibition of the arachidonic acid cascade.…”
Section: L-carnitinementioning
confidence: 98%
“…In conclusion, the findings of this study suggest that endurance training may reverse the MICS found in ESRD that was implicated in the poor prognosis, although we could not determine whether exercise produced an anti-inflammatory effect. Previously, we have reported the effects of L-carnitine supplementation on erythropoietinresistant anemia, [34] cardiac morbidity, [35] and muscle symptoms, [36] all of which are consequences of wasting, and PEM. Most recently, Kalantar-Zadeh et al have demonstrated that an anti-inflammatory and antioxidant nutritional supplement is associated with a significant increase in the serum albumin level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored whether carnitine supplementation in hemodialysis patients results in better function and longevity of the red blood cells, thus decreasing the need for ESA [9,10,11]. We previously reported that anemia, atherosclerosis, and cardiac activity were improved by oral levocarnitine therapy in hemodialysis patients [12].…”
Section: Introductionmentioning
confidence: 99%